Valuation of urban rail service: Experiences from Tokyo, Japan - Hironori Kato (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2014)
Promoting public transportation, which includes rail, metro, bus rapid transit, and bus services is one of the most popular urban transportation policies among transportation authorities in many countries. This popularity may reflect the social requirement to pursue a sustainable transportation system by motivating people to use an environmentally friendly transportation mode. In particular, the modal shift from the automobile to public transportation is highlighted in urban transportation planning because many cities have suffered from serious traffic congestion, which has caused economic losses as well as negative impacts on local, regional, and global environments. In order to attract individuals to use public transportation, the improvement of service is critical. This includes increasing service frequency, decreasing travel time, upgrading station facilities, and introducing higher-capacity vehicles. As most public transportation services are provided directly by public authorities or are financially supported by government/public-sector entities, an investment in public transportation is typically evaluated within a cost-benefit analysis framework. However, since public transportation service consists of many different components, including accessing public transit stops, waiting for the service, riding trains, transferring from one train to another, and exiting to a final destination, it is necessary to evaluate each component in detail. This has made it more difficult to analyze the benefit from public transportation projects than road projects. Thus, there is a strong need to develop a clear methodology by which to value the expected benefits stemming from a public transportation service change in monetary terms according to each service component.
Keywords: 330